Position of Orifice of Distobuccal Canal of Maxillary Second Molars Using Cone-Beam Computed Tomography - Vida M; Shahraki Ebrahimi H; Soltani S; Saberi EA; Pirhaji A (Dove Medical Press, 2020)
Maserat Vida,1 Heshmatallah Shahraki Ebrahimi,2 Sahar Soltani,2 Eshagh Ali Saberi,3 Arezoo Pirhaji2 1Department of Oral and Maxillofacial Radiology, Faculty of Dentistry, Zahedan University of Medical Sciences, Zahedan, Iran; 2Department of Endodontics, Faculty of Dentistry, Zahedan University of Medical Sciences, Zahedan, Iran; 3Department of Endodontics, Faculty of Dentistry, Oral and Dental Diseases Research Center, Zahedan University of Medical Sciences, Zahedan, IranCorrespondence: Eshagh Ali SaberiDepartment of Endodontics, Faculty of Dentistry, Oral and Dental Diseases Research Center, Zahedan University of Medical Sciences, Janbazan Boulevard, 1st and 3rd Janbazan Intermediate, Unit 2, Sistan and Baluchestan, Zahedan, IranTel +98 9151416924Email saberiendo@yahoo.comBackground and Objectives: This study aimed to assess the position of distobuccal canal orifice of maxillary second molars using cone-beam computed tomography (CBCT).Materials and Methods: A total of 301 CBCT scans of patients were retrieved from the archives of a radiology clinic, and the distance between the orifices of distobuccal and mesiobuccal root canals, the distance between the orifices of distobuccal and palatal root canals and the angle between the orifices of mesiobuccal, distobuccal and palatal root canals in the axial plane were measured on CBCT scans.Results: Of 301 maxillary second molars evaluated in this study, 202 (67.1%) had three canals and 99 (32.9%) had four canals. The distance between the distobuccal and mesiobuccal canal orifices (DM) ranged from 1.10 to 4.40 mm (mean: 2.1831± 0.6370 mm). The distance between the distobuccal and palatal canal orifices (DP) ranged from 1.20 to 6.20 mm (mean: 3.8704± 0.84944 mm). The mean angle between the mesiobuccal, distobuccal and palatal orifices (MDP) was 106.37± 12.12075°.Conclusion: Around one-third of maxillary second molars had four canals; the rest had three canals. No maxillary second molar with two canals was found. The orifice of distobuccal canal was located at 2 mm distance from the mesiobuccal canal orifice in distopalatal direction in the majority of cases. It had 3 to 4 mm distance from the palatal canal orifice in most cases. CBCT is recommended to find the orifice of distobuccal canal in cases in whom negotiation of this canal is challenging.Keywords: maxillary second molars, pulp chamber, dental pulp, cone-beam computed tomography